INVERSE SPECTRAL PROPARTIES FOR SYMMETRIC OPERATORS WITH WEYL FUNCTIONS - Abedrahaman, Bashir (Journal of Statistics and Actuarial Research, 2022)
We prove that an operator measure in general is non-orthogonal and unbounded and two orthogonal spectral measures are unitarily equivalent. In accordance with the stieltjes inversion formula the spectral measure admits an analytic continuation .We discuss and prove a sharp estimate that a strictly monotone function on each component interval of the inverse function is analytic and also strictly monotone with Weyl functions.